Investigation of acceptance of driverless buses in the city of Trikala and optimization of the service using Conjoint Analysis. (February 2020) - Papadima, Georgia; Genitsaris, Evangelos; Karagiotas, Ioannis; Naniopoulos, Aristotelis; Nalmpantis, Dimitrios
Abstract: After the completion of the pilot application of the European research project CityMobil2 with driverless buses in the city of Trikala, Greece, which took place from June 2015 to February 2016, there was a need to investigate their acceptance by the passengers. The results of the relevant questionnaire survey show that the residents and the visitors of the area were positive towards the automated vehicles. Moreover, the fact of the positive attitude of the passengers was confirmed by the complementary questionnaire survey conducted using the Conjoint Analysis method regarding the potential optimization of the service. Highlights: The first paper applying Conjoint Analysis to optimize a driverless bus service. People were positive towards the service; as expected for a smart city as Trikala. Encouraged by the city's promotion, while not discouraged by safety concerns. The few who opposed did so due to fear of loss of jobs and parking spaces. The most important attribute was ticket price, as expected.